1999
DOI: 10.1006/dbio.1999.9338
|View full text |Cite
|
Sign up to set email alerts
|

Animal–Vegetal Asymmetries Influence the Earliest Steps in Retina Fate Commitment in Xenopus

Abstract: An individual retina descends from a restricted and invariant group of nine animal blastomeres at the 32-cell stage. We tested which molecular signaling pathways are responsible for the competence of animal blastomeres to contribute to the retina. Inactivation of activin/Vg1 or fibroblast growth factor (FGF) signaling by expression of dominant-negative receptors does not prevent an animal blastomere from contributing to the retina. However, increasing bone morphogenetic protein (BMP) signaling in the retina-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…Previous work demonstrated that the FGF receptor 1 is not required for early Xenopus eye induction or patterning (Kroll and Amaya, 1996), and inactivation of FGF by use of a dominant-negative FGF receptor 1 did not prevent animal blastomeres from contributing to the retina (Moore and Moody, 1999). In contrast, a more recent study in transgenic frogs showed that FGF receptor 4a is required for the correct specification of retinal cell types (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Previous work demonstrated that the FGF receptor 1 is not required for early Xenopus eye induction or patterning (Kroll and Amaya, 1996), and inactivation of FGF by use of a dominant-negative FGF receptor 1 did not prevent animal blastomeres from contributing to the retina (Moore and Moody, 1999). In contrast, a more recent study in transgenic frogs showed that FGF receptor 4a is required for the correct specification of retinal cell types (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…In Xenopus , Noggin can direct the progeny of early blastomeres, not normally destined to contribute to the eyes, to a retinal fate [19],[20]. Human ES cells treated with Noggin, Dickkopf-1, and Insulin-like Growth Factor-1 proteins differentiate into functional photoreceptors [5].…”
Section: Resultsmentioning
confidence: 99%
“…Movies were made using this software and exported as QuickTime movies. Eye volumes were calculated by summing the area of every eye section and multiplying by the section thickness (12 µM) as previously described using Volocity Software [19].…”
Section: Methodsmentioning
confidence: 99%
“…Vertebrate retinal development consists of a series of steps that progressively restrict the available cell fates, and retinal progenitors need to be positioned within the eye field to receive the local environmental signals that will direct their ultimate fate (Huang and Moody, 1993;Moore and Moody, 1999). The retinal precursor cells that give rise to the vertebrate eye field are specified by several transcription factors that both promote retinal fate and control cell movement of progenitor cells during gastrulation and neurulation (Kenyon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%